A Case of Nonalcoholic Steatohepatitis in Central Precocious Puberty Aggravated by Gonadotropin-releasing Hormone Analog. Issue 2 (28th November 2020) - Sasaki, Yoshiaki; Kajino, Hiroki; Gotoda, Hiroko
Abstract : We report the case of a girl with central precocious puberty (CPP) and nonalcoholic steatohepatitis (NASH) aggravated by gonadotropin-releasing hormone analog (GnRHa). She was diagnosed with CCP and began treatment with GnRHa at the age of 8 years and 9 months. She already had mild liver dysfunction and was obese at that time; however, liver dysfunction was aggravated during GnRHa initiation. Her liver dysfunction improved after the discontinuation of GnRHa. Liver biopsy was performed twice during GnRHa initiation and findings suggested NASH. In this case, NASH may have been aggravated by the mechanism of estrogen suppression by GnRHa besides obesity. In conclusion, NASH should be ruled out in obese CPP patients with abnormal liver function before starting GnRHa therapy. CPP patients treated with GnRHa require close examination for the early diagnosis of NASH or its progression.